Phagocytosis, Degranulation and Extracellular Traps Release by Neutrophils—The Current Knowledge, Pharmacological Modulation and Future Prospects - Gierlikowska, Barbara; Stachura, Albert; Gierlikowski, Wojciech; Demkow, Urszula (Frontiers in Pharmacology, 2021)
Neutrophils are crucial elements of innate immune system, which assure host defense via a range of effector functions, such as phagocytosis, degranulation, and NET formation. The latest literature clearly indicates that modulation of effector functions of neutrophils may affect the treatment efficacy. Pharmacological modulation may affect molecular mechanisms activating or suppressing phagocytosis, degranulation or NET formation. In this review, we describe the role of neutrophils in physiology and in the course of bacterial and viral infections, illustrating the versatility and plasticity of those cells. This review also focus on the action of plant extracts, plant-derived compounds and synthetic drugs on effector functions of neutrophils. These recent advances in the knowledge can help to devise novel therapeutic approaches via pharmacological modulation of the described processes.